ANALISIS CORPORATE SOCIAL RESPONSIBILITY PT. NEWMONT NUSA TENGGARA DI WILAYAH KABUPATEN SUMBAWA BARAT PERIODE TAHUN 2009-2013 - Irwansyah, Irwansyah; Sushanti, Sukma; Wisnu Nugraha, A. A. Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2019), 2019)
ABSTRACT This study attempted to analyze Corporate Social Responsibility PT. Newmont Nusa Tenggara in subdistrict Sumbawa Barat period 2009-2013. This research using two concept, namely: first, the concept of multinational corporation in International Political Economy by Steinbockova explaining cooperation pattern that relation MNCs and Nation-states throug CSR. Second, the Concept of Corporate Social Responsibility by kotler-lee explaining philantrophy responsibility  PT. Newmont Nusa Tenggara on human development index in subdistrict Sumbawa Barat. both of concept describe PT. Newmont Nusa Tenggara as MNC can help problem in Sumbawa Barat as new subdistrict in Nusa Tenggara Barat that still need infrastructure and human resources to compete other region. Therefore, there is problem if mine disclosure region to depend on CSR PT. Nusa Tenggara such as job creation and phylantrophy on Sumbawa Barat developing. CSR PT. Nusa Tenggara contributed to improve skill and help to develop local business with Local Business Initiative programme.   Keyword : Corporate Social Responsibility, Human Development Index Sumbawa Barat, Local Business Initiative.